Single-Cell High-Throughput Technologies in Cerebrospinal Fluid Research and Diagnostics - Lanz, Tobias V.; Pröbstel, Anne-Katrin; Mildenberger, Iris; Platten, Michael; Schirmer, Lucas (Frontiers in Immunology, 2019)
High-throughput single-cell technologies have recently emerged as essential tools in biomedical research with great potential for clinical pathology when studying liquid and solid biopsies. We provide an update on current single-cell methods in cerebrospinal fluid research and diagnostics focusing on high-throughput cell-type specific proteomic and genomic technologies. Proteomic methods comprising flow cytometry and mass cytometry as well as genomic approaches including immune cell repertoire and single-cell transcriptomic studies are critically reviewed and future directions discussed.